KAEMPFEROL EXERTS A DIFFERENTIAL EFFECT ON KB ORAL CARCINOMA CELLS AND NORMAL HUMAN BUCCAL CELLS - SIVADOSS SIVAPRIYADHARSHINI,; PALGHAT RAGHUNATHAN PADMA, (International Journal of Pharma and Bio Sciences, 2016)
Kaempferol is a natural plant derived flavonoid that has been shown to possess potent anticancer activity against several cancer cells, but the differential effect of the compound on oral cancer cells and normal oral cells is largely unknown. In the present study, we attempted to identify the apoptosis-inducing ability of kaempferol in KB oral cancer cell line and its effect on cultured normal human buccal cells. MTT and SRB assays showed that kaempferol significantly reduced the viability of KB cells, whereas in normal buccal cells, the viability was comparatively higher. Fluorescent staining of kaempferol treated KB cells showed changes in nuclear morphology typical to apoptotic cells. Kaempferol induced a G2/M phase cell cycle arrest in KB cells, as shown by flow cytometry.